The Current Status and Development of Rehabilitation Landscape Design in Outdoor Spaces of Comprehensive Hospitals in China (International Journal of Built Environment and Sustainability, 2025)
This paper systematically investigates the development trends and research focuses on rehabilitation landscape design in Chinese hospital settings over the past three decades. Firstly, through an analysis of publication volume and time, the different stages of hospital landscape design development are elaborated, emphasising trends correlated with national policies and epidemic factors. Secondly, employing keyword clustering and time-tagged visualisation techniques, the research hotspots of comprehensive hospital rehabilitation landscape design, such as rehabilitation landscape design, comprehensive hospitals, and horticultural therapy, are highlighted. Furthermore, an extensive selection and analysis of relevant articles and books are conducted, summarising the developmental characteristics of rehabilitation landscape design in terms of functionality, therapeutic qualities, humanisation, sustainability, and cultural inheritance and innovation. Lastly, the paper calls for future research to focus on the correlation between patient experience and treatment outcomes, interdisciplinary collaboration and integrative design approaches, sustainability, and eco-friendly design, as well as the application of digital technology in landscape design, to drive continuous innovation and advancement in the field of hospital rehabilitation landscape design
Keywords: General Hospital, Outdoor Landscape, Rehabilitation Landscape Design